Evaluación de la adaptabilidad de seis variedades mejoradas de trigo (triticum aestivun l). mediante el apoyo de investigación participativa en las localidades el Chan y San Ramón del canton Latacunga, Cotopaxi - Chuquitarco Guanoluisa, Paulina Guadalupe (2015)
The research was made in San Ramon and Chan neighborhood. The item entitled Evaluation of the adaptability of six varieties improved of wheat (Triticum L. aestivun) through the support participatory research in San Ramon and Chan neighborhood, Latacunga canton, Cotopaxi province. The experimental method (DBCA) randomized complete block design was used in a total area of 640 m2, settle three replicate each with 7 treatments giving a total of 21T for each location For which variables were evaluated: days to germination, number of tillers per plant, days to flower development, size stem, incidence of pests, plant height, number of grains per spike, weight test, days to harvest.